Contrast Enhanced Echocardiography-Controlled Alcohol Septal Ablation for Hypertrophic Cardiomyopathy with Left Ventricular Outflow Tract Obstruction - I. E. Nikolaeva; V. V. Plechev; A. M. Mukhametyanov; R. M. Biktashev; I. V. Buzaev; G. A. Khalikova (Креативная хирургия и онкология, 2019)
In the SFHI (State Funded Healthcare Institution) Republic’s Centre for Cardiology the method of alcohol septal ablation has been introduced in 2015. The paper presents one case of a successful treatment of a patient with hypertrophic cardiomyopathy with left ventricular outflow tract obstruction treated with the use of the method of alcohol septal ablation under control of contrast enhanced echocardiography of the ablation area in the interventricular septum.